MATERNAL AND PATERNAL PARENTING STYLES: ASSESSMENT AND RELATIONSHIP WITH ADOLESCENT ADJUSTMENT - Oliva Delgado, Alfredo; Parra Jiménez, Águeda; López Gaviño, Francisca; Sánchez Queija, Inmaculada (Anales de Psicología / Annals of Psychology, 2007)
This study presents the validation of a scale that was elaborated to assess maternal and paternal parenting styles according to the percep-tion of their adolescent children. The scale was applied to a sample composed by 848 adolescents aged from 12 to 17 years old, that also filled out the Youth Self Report, a life satisfaction scale and a substance use question-naire. Exploratory and confirmatory factor analyses revealed a six factors structure for maternal and also for paternal parenting style. These dimen-sions showed significant relationships with most of the measures of ado-lescent adjustment considered in the study. Comparisons between boys’ and girls’ perceptions of paternal and maternal parenting styles revealed that, in spite of the high agreement between both styles, mothers were scored higher than fathers in every dimension of parenting style.